Mnenje uporabnikov električnih protez v Sloveniji o pomenu zaznavanja s protezo - Burger, Helena (Rehabilitacija (Ljubljana), 2020)
Background: The main limitation of current upper limb prostheses is lack of sensation. We wanted to find out the opinion of upper-limb prosthesis users in Slovenia about the importance of sensation with prosthesis, how important are for them the activities for which sensation is important, and about advantages and disadvantages of their myoelectric prosthesis. Methods: We prepared a survey with 14 questions and sent it together with information about the project, informed consent and post envelope with stamp and our address on it to all current users of a myoelectric prosthesis in Slovenia or those who had worn it in the last ten years, aged at least 18 years; altogether to 34 people. Results: We received 11 answers. For seven myoelectric prosthesis users, it is extremely important that they can feel with the prosthetic hand and also manipulate fragile objects, followed by the ability to clean the glove. Ten respondents would want to feel the touch of the object, nine the sliding of the object and the grip force, and seven to also feel the temperature of the object. Six participants preferred to get information via vibration, two with vision, one by vision and sound, and one by vision and vibration.
Keywords: amputacija; amputation; prostheses; Prostheses and Implants; proteze; raznavanje; rehabilitacija; rehabilitation; rehabolitation; sensation; Upper Extremity; upper limb; zgornji ud